Percutaneous Treatment of Biliary Complications in Pediatric Patients After Liver Transplantation - Uller, W.; Wohlgemuth, W. A.; Hammer, S.; Knoppke, B.; Goessmann, H.; Loss, M.; Schlitt, H. J.; Stroszczynski, C.; Zorger, N.; Heiss, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Evaluation of the efficiency and safety of the percutaneous treatment of biliary complications in pediatric liver transplant recipients.Methods: We conducted a retrospective analysis of children who underwent biliary percutaneous interventions after pediatric liver transplantation (PLT) over a 4-year period. Kind of biliary complication, interval between liver transplantation and intervention, status of the vessels, procedural interventional management, technical and clinical success, course of cholestasis, PTBD-related complications and patient survival were analyzed.Results: 23 percutaneous transhepatic biliary drainages (PTBD) were placed in 16 children due to 18 biliary complications. The drains were customized individually by shortening and cutting additional holes. PTBD placement was performed with technical and clinical success in all children. 4 children received PTBD to bridge the time to retransplantation and surgical revision. One child received PTBD for successful treatment of anastomotic leakage. Long-term dilation of biliary stenoses was performed in 13 children using PTBD. One of these 13 patients showed recurrent stenosis during a median follow-up of 295 days. Bilirubin values decreased significantly after PTBD placement for biliary stenosis. One patient suffered from bacteremia after PTBD replacement.Conclusion: PTBD treatment for biliary complications after PLT is effective and safe. Key points: Various biliary complications after PLT can be successfully treated by PTBD. For this purpose, a highly individualized approach with catheter modification is mandatory.Citation Format:• Uller W, Wohlgemuth WA, Hammer S et al. Percutaneous Treatment of Biliary Complications in Pediatric Patients After Liver Transplantation. Fortschr Röntgenstr 2014; 186: 1127 – 1133
Keywords: bile ducts; bile duct radiography; percutaneous; catheters; cholangitis; transplantation